Mediterranean resilience collapse and adaptation in antique maritime societies - Yasʿur-Landau, Assaf 1973-; Gambash, Gil 1973-; Levy, Thomas Evan 1953- (New directions in anthropological archaeology, 2024)
"The aim of this volume is to examine various forms of adaptation adopted by coastal societies in the ancient Mediterranean in response to external pressures they occasionally experienced. The investigation spans the longue durée stretching from the epi-paleolithic to the Medieval period."